Approximation by overconvergent power series - B. Schillings (Հայաստանի ԳԱԱ)
The paper gives a short survey of resuls on approximation by overconvergent power series and discusses the question of possible lacunas of power series representing the universal functions.
Keywords: Mathematics; Science